Factors associated with the completeness of K6 antenatal care examinations among pregnant women - Inggit Primadevi; Nur Alfi Fauziah; Septika Yani Veronica; Tri Lusi Setiowati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The Maternal Mortality Rate (MMR) in Pringsewu Regency increased from 16 per 100.000 live births in 2023 to 194 per 100,000 live births in 2024. One of the key efforts to reduce MMR is ensuring comprehensive Antenatal Care (ANC) visits, including the minimum standard of six visits (K6). However, the K6 coverage at Adiluwih Health Center in 2024 remained relatively low at 66.8%. Purpose: To identify the factors associated with the completeness of K6 examinations among pregnant women. Method: This research is a quantitative study with a cross-sectional approach. The population consisted of postpartum mothers at Adiluwih Health Center from January to April 2025, and the sample included 81 respondents, representing the total population. The data used were secondary data obtained from maternal and child health (MCH) books. The statistical test employed was the Chi-Square test. Results: The results showed that most respondents had good knowledge (48 respondents; 59.3%), a positive attitude (60 respondents; 74.1%), supportive family support (71 respondents; 87.7%), supportive health worker assistance (70 respondents; 86.4%), and complete K6 examinations (57 respondents; 70.4%). Conclusion: Statistical analysis indicated significant relationships between knowledge, attitude, family support, and health worker support and the completeness of K6 examinations among pregnant women (p-value < 0.05). Suggestion: is expected that pregnant women undergo at least six antenatal visits according to standards during pregnancy, with at least two of these visits conducted by a doctor during the first and third trimesters.